Influence of Digital Marketing and Online Customer Reviews on Customer Satisfaction: A Case Study of Husna Frozen Mart - Ferdiyanto, Rafli; Sahara, Sahara; Kustandi, Tedi (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to examine the influence of digital marketing and online customer reviews on customer satisfaction with Husna Frozen Mart’s products, and to provide insights into factors that drive consumer loyalty through satisfaction. Methodology: The research employed a quantitative approach using a survey method, distributing questionnaires to Husna Frozen Mart customers. Data were analyzed through multiple linear regression, supported by validity and reliability tests, as well as t-tests, F-tests, and the coefficient of determination (R².. Results: The findings reveal that digital marketing has a positive and significant effect on customer satisfaction. Likewise, online customer reviews exert a positive impact, though at a different magnitude. When tested simultaneously, both independent variables significantly affect customer satisfaction. Findings: The study highlights that consistent digital marketing strategies combined with online customer reviews contribute to enhanced customer satisfaction, particularly in terms of information accessibility, product trustworthiness, and purchase decision-making. Novelty: This research addresses a gap in the literature by jointly analyzing digital marketing and online customer reviews within the context of a local frozen food MSME, a setting that has received limited scholarly attention, especially in Cirebon. Originality: Unlike prior studies that focused on large enterprises or online marketplaces, this study specifically investigates Husna Frozen Mart as a local MSME, offering a fresh perspective on the role of digital marketing and customer reviews in small business competitiveness. Conclusion The study concludes that effective digital marketing implementation and proactive management of online customer reviews significantly improve customer satisfaction. These findings serve as a practical foundation for MSMEs to strengthen their competitive position in the digital era. Type of Paper: Empirical research paper.